Case Study: Effect of CO-PO Mapping and Attainment on Third-Year B Pharm Students - Chaudhari, Shilpa Pravin; Powar, Priyatama Vijaysing; Nikam, Sarika Ankushrao (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background This paper discusses a case study using CO-PO mapping and accomplishment for Tier II institutes' third-year B.Pharm students. It is required to be outcome-based education in accordance with the National Board of Accreditation's June 2015 scheme. There are observable disparities in students' employability when it comes to the acquisition of professional expertise and abilities and the growth of an attitude of professionalism. Tier II students have a significant chance to close the placement and higher education gap by following the guidelines outlined in NBA Manual Criteria 3 on CO-PO mapping and accomplishment. Materials and Methods In the current paper, with help of third year B Pharm students we tried to established rubrics assessment and use of algorithm suggest a systematic approach to continual enhancement strategy that teachers and students in the pharmacy stream can readily apply. Results On mapping each CO with each PO and using different techniques to bridge the gaps significantly improves performance of student as the orientation is changed. Conclusion Applicability of OBE in curriculum is welcoming by students and will give desired outcomes if implemented properly.
Keywords: CO-PO attainment; CO-PO mapping; Employability; Learning Objective; Learning Outcome; Outcome Based Accreditation; Program Outcomes.